Preferred and Non-Preferred Creditors - Cordella, Tito; Powell, Andrew (World Bank, Washington, DC, 2019)
International financial institutions (IFIs) generally enjoy preferred creditors treatment (PCT). Although PCT rarely appears in legal contracts, when sovereigns restructure bilateral or commercial debts they normally pay IFIs in full. This paper presents a model where a creditor, such as an IFI, that can commit to lend limited amounts at the risk-free rate and can refrain from lending into arrears is always repaid and adds value. The analysis suggests that IFIs should not mimic commercial lenders, but exploit their complementarity, even if banning commercial borrowing can sometimes be optimal. IFIs should also focus on countries with limited market access and should not be forced into debt restructurings.